Memórias que narram a cidade: a trajetória de dois imigrantes portugueses em Foz do Iguaçu - Cabanha, Samuel (2017)
This study deals with some elements of Portuguese immigration in Foz do Iguaçu from 1957 to 2016. It explores the memories and travels of experiences of two Portuguese immigrants in Foz do Iguaçu, in order to show how the memories surfaced in the interview narrated to the city and To your sample group. The methodology adopted was the qualitative research, following theoretical-methodological assumptions of the Oral History, and the data collection consisted of classic documentary research, and partial use of oral sources through interviews and printed sources (photographs, Newspaper articles, websites and a court case). Briefly, the theory framework revolves around discussions that involve concepts related to immigration, memory, and identity, showing how Portuguese memories that surfaced in the interviews and in the group's activities act as identity markers. As a result, the study reconstructs some details of the travel, the daily life, the material life of the deponents and the group of Portuguese immigrants in Foz do Iguaçu. In this way, it demonstrates how the identity of the group was influential so that they built for themselves a place of memory "The House of Portugal", and leaves some crumbs that tell a little of the comings and goings of the Portuguese community in the municipality of Foz do Iguaçu. In this sense, research on the Portuguese community in Foz do Iguaçu impacts the studies on multiculturalism in the region, and serves as a fundation and opening for future studies.